Oligomerization of KCC2 Correlates with Development of Inhibitory Neurotransmission - Blaesse, Peter (J Neurosci, 2006)
The neuron-specific K(+)–Cl(−) cotransporter KCC2 extrudes Cl(−) and renders GABA and glycine action hyperpolarizing. Thus, it plays a pivotal role in neuronal inhibition. Development-dependent KCC2 activation is regulated at the transcriptional level and by unknown posttranslational mechanisms. Here, we analyzed KCC2 activation at the protein level in the developing rat lateral superior olive (LSO), a prominent auditory brainstem structure. Electrophysiology demonstrated ineffective KCC2-mediated Cl(−) extrusion in LSO neurons at postnatal day 3 (P3). Immunohistochemical analyses by confocal and electron microscopy revealed KCC2 signals at the plasma membrane in the somata and dendrites of both immature and mature neurons. Biochemical analysis demonstrated mature glycosylation pattern of KCC2 at both stages. Immunoblot analysis of the immature brainstem demonstrated mainly monomeric KCC2. In contrast, three KCC2 oligomers with molecular masses of ∼270, ∼400, and ∼500 kDa were identified in the mature brainstem. These oligomers were sensitive to sulfhydryl-reducing agents and resistant to SDS, contrary to the situation seen in the related Na(+)–(K(+))–Cl(−) cotransporter. In HEK-293 cells, coexpressed hemagglutinin-tagged KCC2 assembled with histidine-tagged KCC2, demonstrating formation of homomers. Based on these findings, we conclude that the oligomers represent KCC2 dimers, trimers, and tetramers. Finally, immunoblot analysis identified a development-dependent increase in the oligomer/monomer ratio from embryonic day 18 to P30 throughout the brain that correlates with KCC2 activation. Together, our data indicate that the developmental shift from depolarization to hyperpolarization can be determined by both increased gene expression and KCC2 oligomerization.